2023
DOI: 10.53730/ijhs.v7n1.13843
|View full text |Cite
|
Sign up to set email alerts
|

How to assess nurse learning needs through training needs analysis

Abstract: Training has a very important role in improving the performance of nurses. This study aims to assess nurses' learning needs through the training needs of nurses. This study used a mixed-methods design. The first phase involved an online survey. The second phase of qualitative research involved conducting structured interviews with 8 nurses. A total of 413 nurses participated in this survey. Nurses' competence was found in the competence of meeting fluid and electrolyte needs with a mean of 3.8 (SD: 0.7), the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The foundation of designing a unit orientation program, whether for nurses new to the nursing profession or experienced nurses new to the organization or unit, is a learning needs assessment. 10 The needs assessment helps to develop a personalized educational plan that also helps the new nurse acquire the tools and knowledge to provide excellent care that meets the standards of care for infants and children with heart disease. A self-assessment of skills and knowledge is then followed up with skill validation or checklists and targeted education.…”
Section: New Hire Orientation and Competency Assessmentmentioning
confidence: 99%
“…The foundation of designing a unit orientation program, whether for nurses new to the nursing profession or experienced nurses new to the organization or unit, is a learning needs assessment. 10 The needs assessment helps to develop a personalized educational plan that also helps the new nurse acquire the tools and knowledge to provide excellent care that meets the standards of care for infants and children with heart disease. A self-assessment of skills and knowledge is then followed up with skill validation or checklists and targeted education.…”
Section: New Hire Orientation and Competency Assessmentmentioning
confidence: 99%
“…The results of discussions and interviews also found that training venues are more effectively held internally because they can save time, costs, and human resources. The previous study found mixed training is the most desirable one (Sudarmika et al, 2023). Mixed learning is a combination of online learning and face-to-face learning which is called blended (Nasution et al, 2019).…”
Section: Reaction Evaluationmentioning
confidence: 99%
“…The results of the preliminary study found that as much as 47.2% liked the mixed training model (face-toface and online), as much as 86.4% liked training through e-learning and as much as 78.9% liked audio-visual media compared to PowerPoint media, and text modules (Sudarmika et al, 2023). To find out the results, impacts, and benefits obtained from the training provided to employees, it is necessary to evaluate each training.…”
Section: Introductionmentioning
confidence: 99%